Regulation of Monocyte Tissue Factor Activity by Allogeneic and Xenogeneic Endothelial Cells - Kopp, Christoph W.; Robson, Simon C.; Siegel, Jonathan B.; Anrather, Josef; Winkler, Hans; Grey, Shane; Kaczmarek, Elzbieta; Bach, Fritz H.; Geczy, Carolyn L. (Thrombosis and Haemostasis, 1998)
The regulation of tissue factor (TF) activity by the cell associated tissue factor pathway inhibitor (TFPI) during monocyte (Mo) and endothelial cell (EC) interactions is not fully understood. This report describes co-ordinate induction of TF antigen (TF-Ag) and membrane-associated TFPI-Ag on human Mo following coculture with human aortic (HAEC) or porcine aortic EC (PAEC) or after stimulation with TNFα. We show that both allo- and xenogeneic EC induce human Mo-TF antigen in short-term culture. However, the TF activity of TNFα-primed Mo is suppressed when these cells are cocultured with HAEC [by 40.3 ± 6.3% (p <0.02)] or PAEC [by 50.5 ± 10.6% (p <0.001)]. Antibody (Ab) blocking studies confirm that TFPI is the principal anticoagulant associated with this suppression of TF-activity. Our data indicate that anti-TF activity originates, at least in part, from the activated human Mo in the coculture; additionally, specific generation of TFPI by Mo is observed under the xenogeneic culture conditions. As Mo associated TF, induced by allo- or xenogeneic EC interactions, is regulated by cell-associated TFPI, we propose that infiltrating Mo may modulate the thrombotic process at sites of vascular injury in association with both allo- and xenograft rejection.Aspects of the work were presented at the American Society for Hematology meeting in Orlando, FL, December 1996.